Financial Statement Analysis to Evaluate the Financial Performance of PT Astra International Tbk - Fitrianti Nurtika; Alamsjah Alamsjah; A. Tenri Syahriani (Pustaka Digital Indonesia, 2026)
This study is urgent because evaluating the financial performance of PT Astra International Tbk through financial statement analysis provides critical insights into the company’s financial resilience, strategic effectiveness, and sustainability amid economic uncertainty and intense industry competition. This study analyzes the financial performance of PT Astra International Tbk over the 2019–2023 period using a descriptive quantitative approach based on secondary financial data published by the Indonesia Stock Exchange (IDX). The purpose of this research is to evaluate the company’s financial condition through four key financial ratio categories: liquidity, solvency, profitability, and activity. Time series analysis was employed to identify trends and changes occurring across the five-year period. The findings indicate that PT Astra International Tbk maintained strong liquidity, as reflected by consistently favorable current and quick ratios, despite slight declines beginning in 2022. Solvency analysis shows that the company gradually reduced its debt burden until 2022, although a modest increase in 2023 suggests renewed reliance on external financing. Profitability ratios including gross profit margin, net profit margin, and return on assets demonstrated notable improvement following the economic disruption of 2020, indicating effective cost management and enhanced operational efficiency. Activity ratios also showed positive trends, with asset turnover and inventory turnover reflecting efficient utilization of resources and strong sales performance. Overall, the study concludes that PT Astra International Tbk exhibited resilient and improving financial performance throughout the observation period, supported by prudent financial management and adaptive strategies in response to macroeconomic challenges. These results highlight the importance of integrated financial ratio analysis for assessing corporate financial health and informing strategic business decisions.